Analisis Hukum terhadap Status Pernikahan Beda Agama dan Implikasinya terhadap Hak Waris di Indonesia - Yani Andriyani; Amelya Julianti; Iman Jalaludin Rifa’i (Universitas Kuningan, 2025)
This study aims to analyze the law on interfaith marriage and its implications for inheritance rights in Indonesia. The research method used is a normative approach by examining and interpreting theoretical matters concerning legal principles. The results of this study indicate that interfaith marriage is strictly prohibited in Islam. This has been explained in the Compilation of Islamic Law, Article 40 letter c and Article 44 explicitly regulate the prohibition of marriage between Muslim men and non-Muslim women and Muslim women and non-Muslim men. Regarding the settlement of inheritance rights for children born from interfaith couples according to the perspective of Islamic Inheritance Law, children born from interfaith marriages do not have the right to inherit property if they are not of the same religion as the testator, in this case the testator is Muslim. However, if the testator is not Muslim (non-Muslim), while the heirs are not of the same religion as the testator, then they still have the right to inherit based on the blood relationship between the testator and the heirs which is explained in Article 832 of the Civil Code and Article 171 letter c of the Compilation of Islamic Law (KHI). From this research, it can be concluded that interfaith marriages not only violate religious principles but also have significant legal implications regarding inheritance rights for children resulting from such marriages and there must be improvements to existing laws to provide legal certainty regarding the legal status of interfaith marriages and especially those related to inheritance.